The Influence Of Financial Literacy And Perceptions Of Financial Risk On The Decision To Use Shopee Paylater Among Students At The Faculty of Economics And Business, University Of Mataram - Tyas Septianingsih; Baiq Anggun Hilendri Lestari; Rini Ridhawati (Cita Konsultindo Research Center, 2024)
The growth of e-commerce platforms and applications sold online is the impact of technological progress technology. Along with many feature applications, selling keeps buying online continuously increasing, and payments also increase quickly and more comfortably. The growth of internet technology is one of the forces driving e-commerce. More and more people are using the internet to shop because access is increasingly economical. Usability for online purchases, including buying and selling procedures, becomes more straightforward with